Activity of radionuclides in soils contaminated by scrap iron residues in the first (1st) district of Cotonou (Bénin) - Hounsou, Francis Théotime Mahudjro; Avocefohoun, Alphonse S.; YOUSSAO ABDOU KARIM, ALASSANE; AKOMONLA, Christian; Montcho, Papin Sourou; GBAGUIDI, AHOTONDJI BERTIN; BABA-MOUSSA, LAMINE SAÏD; AMOUSSOU-GUENOU, KUASSI MARCELLIN (My University, 2022)
The scrap metal waste export activity has proliferated in Bénin and in the West African sub-region in recent decades. It is a sector that employs a growing number of workers, particularly on the former SONICOG site in the first district of Cotonou in Bénin. Unfortunately, this scrap metal waste can constitute chronic sources of radioactive contamination of the soil and of exposure of populations to ionizing radiation. The aim of this research work is to estimate the specific activities of the soil and the radionuclides involved on the site of the former SONICOG scrap metals, which has been in operation for more than two decades. The methodological approach consisted in taking soil samples using the diagonal method and analyzing them by gamma spectrometry using a Baltitic Scientific Instrument, Ltd (BSI) type device fitted with GammaPro analysis software. The results show a stronger contamination of the superficial horizons by radionuclides such as lead (212Pb), thorium (232Th), cesium (137Cs) in general and compared to the control soil. On the other hand, potassium (40K) is detected only in the surface horizon of the soil1 while actinium (228Ac) was found in the first two surface horizons of the soil2; as for americium (241Am), it has been detected in the soil3 but it is not quantifiable (low concentrations). Moreover, all these radioelements are in low quantity in the control sample (soil0) chosen as the reference soil. This observation, coupled with an unequal distribution of radioactive sources in the soil horizons, confirms the hypothesis that the radioactive sources come from ferrous and non-ferrous metals from scrap metal waste on the various sites. Workers in the scrap metal sorting-recycling chain risk the effects of direct chronic exposure to low doses of ionizing radiation emitted by these sources and populations from indirect exposure.
Keywords: scrap metal; contaminated soil; ionizing radiation; radionuclides; Cotonou